PRAKTIK HAMBATAN KOMUNIKASI ANTAR BUDAYA: Stereotyping DI OMETV - Chelvin Trisna (2022)
The results of this study indicate that there are barriers to intercultural communication in the open space of OmeTV social media, namely the practice of Stereotyping in the form of verbal and text from one user to another. Stereotyping practices that exist on OmeTV are caused by the personal background of users who are currently on OmeTV, then the openness of the platform causes users to feel free to express whatever they want, and the lack of awareness of users to respect each other when they are in the room. OmeTV social media is open because we ourselves have to control the exchange of information on OmeTV. When a user is able to control what he actually does on OmeTV, there is a high probability that Stereotyping practices will occur on OmeTV.